Impact of polydextrose on the faecal microbiota: a double-blind, crossover, placebo-controlled feeding study in healthy human subjects - Costabile, Adele; Fava, Francesca; Röytiö, Henna; Forssten, Sofia D.; Olli, Kaisa; Klievink, Judith; Rowland, Ian R.; Ouwehand, Arthur C.; Rastall, Robert A.; Gibson, Glenn R.; Walton, Gemma E. (British journal of nutrition, 2012)
In this placebo-controlled, double-blind, crossover human feeding study, the effects of polydextrose (PDX; 8 g/d) on the colonic microbial composition, immune parameters, bowel habits and quality of life were investigated. PDX is a complex glucose oligomer used as a sugar replacer. The main goal of the present study was to identify the microbial groups affected by PDX fermentation in the colon. PDX was shown to significantly increase the known butyrate producer Ruminococcus intestinalis and bacteria of the Clostridium clusters I, II and IV. Of the other microbial groups investigated, decreases in the faecal Lactobacillus–Enterococcus group were demonstrated. Denaturing gel gradient electrophoresis analysis showed that bacterial profiles between PDX and placebo treatments were significantly different. PDX was shown to be slowly degraded in the colon, and the fermentation significantly reduced the genotoxicity of the faecal water. PDX also affected bowel habits of the subjects, as less abdominal discomfort was recorded and there was a trend for less hard and more formed stools during PDX consumption. Furthermore, reduced snacking was observed upon PDX consumption. This study demonstrated the impact of PDX on the colonic microbiota and showed some potential for reducing the risk factors that may be associated with colon cancer initiation.